ChemInform Abstract: Synthesis of Oxygenated 4‐Arylisoflavans and 4‐Arylflavans. Issue 13 (18th March 2013) - Deodhar, Mandar; Wood, Kasey; StC Black, David; Kumar, Naresh
Abstract A simple protocol allows the arylation of the isoflavon‐4‐ol mixture (I) to give 4‐arylated products (III) with trans diastereoselectivity.